How do you simplify (-1)(-2+3)-(4-9)(-2)?

2 Answers
Nov 12, 2015

-11.

Explanation:

We use BIDMAS/PEDMAS for this operation. So,
we start with the brackets, adding all values inside a specific bracket:
(-2+3) = (1),
(4-9) = (-5).

We have added all values within brackets. Now we have:
(-1)(1)-(-5)(-2). We have no exponentials/indices nor divisions, so we move on to multiplications:
(-1)(1) = (-1),
(-5)(-2) = (10).

We have multiplied. Now we've got:
(-1) - (10) = -11.

Hope it Helps! :D .

Aug 1, 2016

-11

Explanation:

Count the number of terms first. There are only 2, but there are parentheses in each term which need to be worked out first.

color(red)((-1)(-2+3)) color(blue)(- (4-9)(-2))
=color(red)((-1) xx (1)) - color(blue)((-5)(-2))

=color(red)-1 - color(blue)(10)

=-11